Perencanaan Keamanan Informasi Berdasarkan Analisis Risiko Teknologi Informasi Menggunakan Metode OCTAVE dan ISO 27001 (Studi Kasus Bidang IT Kepolisian Daerah Banten) - Fadzri Ahdi Anshori; Suprapto Suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Banten Regional Police is a public service provided by the government to secure and enforce the law in force in Indonesia, especially in urban areas. Operational activities at the Banten Regional Police have been supported by information technology, but the application of information technology in Banten Regional Police has not had a policy regarding information security and risk management. The purpose of this study is to provide a risk mitigation plan that is appropriate for the Banten Regional Police. Provisions on risk mitigation plans can be obtained by identifying and assessing the risks in the Banten Regional Police based on the OCTAVE method. Risk mitigation recommendations are provided in accordance with ISO 27001 standards and prioritized based on the costs and benefits of each recommendation action. The final results of this study, there are 28 risks that may occur in Banten Regional Police with the highest RPN value 240 to the lowest RPN value 18. Risk mitigation recommendations can be made with 11 controls contained in ISO27001.